Subminute thermal damage to cell types present in the skin - Meagan Doppegieter; Ton G. van Leeuwen; Angela van Weert; Maurice C.G. Aalders; Erik N.T.P. Bakker (International Journal of Hyperthermia)
Introduction Psoriasis is characterized by an increase in the proliferation of keratinocytes and nerve fiber activity, contributing to the typical skin lesions. Pulsed Dye Laser (PDL) treatment is effective for the treatment of psoriatic lesions but its mechanism remains unclear. One hypothesis is that PDL causes thermal damage by the diffusion of heat to neighboring structures in lesional skin. There is limited information on the thermal sensitivity of these neighboring skin cells when exposed to hyperthermia for durations lasting less than a minute. Our study aimed to investigate the cell-specific responses to heat using sub-minute exposure times and moderate to ablative hyperthermia.Materials and Methods Cultured human endothelial cells, smooth muscle cells, neuronal cells, and keratinocytes were exposed to various time (2–20 sec) and temperature (45–70 °C) combinations. Cell viability was assessed by measuring intracellular ATP content 24 h after thermal exposure and this data was used to calculate fit parameters for the Arrhenius model and CEM43 calculations.Results Our results show significant differences in cell survival between cell types (p < 0.0001). Especially within the range of 50–60 °C, survival of neuronal cells and keratinocytes was significantly less than that of endothelial and smooth muscle cells. No statistically significant difference was found in the lethal dose (LT50) of thermal energy between neuronal cells and keratinocytes. However, CEM43 calculations showed significant differences between all four cell types.Conclusion The results imply that there is a cell-type-dependent sensitivity to thermal damage which suggests that neuronal cells and keratinocytes are particularly susceptible to diffusing heat from laser treatment. Damage to these cells may aid in modulating the neuro-inflammatory pathways in psoriasis. These data provide insight into the potential mechanisms of PDL therapy for psoriasis and advance our understanding of how thermal effects may play a role in its effectiveness.